An implementation of vision based deep reinforcement learning for humanoid robot locomotion - Özalp, Recep; Kaymak, Çağrı; Yıldırım, Özal; Uçar, Ayşegül, Demir, Yakup, Güzeliş, Cüneyt (My University, 2019)
An implementation of vision based deep reinforcement learning for humanoid robot locomotion
Bildiri - Yayımlanmış
Keywords: İnsansı robotlar; Derin öğrenme